The Effect of Capital, Bussiness Duration, and Working Hours on the Income of Tilapia Fish Traders at Angso Duo Market in Jambi City - Sitanggang, Yolanda Patrecia; Hodijah, Siti; Nurjanah, Rahma (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of capital, business duration, and working hours on the income of tilapia fish traders at Angso Duo Market in Jambi City. Research Methods: This research employs a descriptive quantitative approach using primary data obtained through observation, questionnaires, interviews, and documentation. The study involves 48 respondents selected using a saturated sampling technique. Finding/Results: The results show that, simultaneously, capital, business duration, and working hours have a significant effect on income, with a coefficient of determination (R²) of 0.549. Partially, all three variables also have a positive and significant effect on income. Conclusion: In conclusion, increasing capital, business experience, and working hours can enhance traders’ income. Traders are encouraged to optimize their capital and working hours, while support in terms of access to capital from relevant stakeholders is also essential.